LEGAL PROTECTION FOR WORKERS ON OCCUPATIONAL SAFETY AT PT. MEGA RAYA PROPERTY - Kaenama Muhammad, Yunan; Marlina, Tina; Maulida, Irma (Hukum Responsif, 2024)
The implementation of occupational safety has the primary goal of improving and maintaining all workers' physical, mental, and social welfare in all types of work, preventing health problems caused by work, and avoiding accidents during work. Cirebon is one area famous for its significant progress in industrial development, one of which is in the construction sector. These jobs have a high risk of work accidents during the construction process of construction projects because work safety standards are still inadequate. This is evidence of the lack of attention to the importance of occupational safety in construction work. In this study, a normative juridical approach method is used, namely literature law research, which is carried out by researching library materials or secondary data. Then, it continued with the collection of primary material data through direct interviews and observations as well as secondary materials obtained from literature studies in the form of law books, legal journals, and other literacy associated with the core of this research. The study results show that: (1) The form of legal protection in PT. Mega Raya Property uses a form of preventive legal protection because the company uses its policies in the employment agreement in the form of an oral agreement, so the form of legal protection for workers is not optimal because workers do not get their rights optimally and clearly if something happens. (2) The efforts to resolve work accident cases experienced by workers have been carried out based on the policy of PT. Mega Raya Property is per Government Regulation Number 82 of 2019 concerning the Implementation of Work Accident Insurance and Death Insurance Programs, and the final results are determined based on mutual agreement.